What is behind smoker support for new smokefree areas? National survey data - Wilson Nick; Weerasekera Deepa; Blakely Tony; Edwards Richard; Thomson George; Gifford Heather (BMC Public Health, 2010)
Abstract Background Some countries have started to extend indoor smokefree laws to cover cars and various outdoor settings. However, policy-modifiable factors around smoker support for these new laws are not well described. Methods The New Zealand (NZ) arm of the International Tobacco Control Policy Evaluation Survey (ITC Project) derives its sample from the NZ Health Survey (a national sample). From this sample we surveyed adult smokers (n = 1376). Results For the six settings considered, 59% of smokers supported at least three new completely smokefree areas. Only 2% favoured smoking being allowed in all the six new settings. Support among Maori, Pacific and Asian smokers relative to European smokers was elevated in multivariate analyses, but confidence intervals often included 1.0. Also in the multivariate analyses, "strong support" by smokers for new smokefree area laws was associated with greater knowledge of the second-hand smoke (SHS) hazard, and with behaviours to reduce SHS exposure towards others. Strong support was also associated with reporting having smokefree cars (aOR = 1.68, 95% CI = 1.21 - 2.34); and support for tobacco control regulatory measures by government (aOR = 1.63, 95% CI = 1.32 - 2.01). There was also stronger support by smokers with a form of financial stress (not spending on household essentials). Conclusions Smokers from a range of population groups can show majority support for new outdoor and smokefree car laws. Some of these findings are consistent with the use of public health strategies to support new smokefree laws, such as enhancing public knowledge of the second-hand smoke hazard.